Multidisciplinary approach to safety of antithrombotic therapy: focus on the gastrointestinal tract - Natalia Yu. Borovkova; Marina V. Buyanova (LLC "MEDIAFORMAT", 2021)
Multidisciplinary approach to safety of antithrombotic therapy used in clinical practice is reported. Such complications of antithrombotic therapy as gastrointestinal tract (GIT) erosion/ulceration and gastrointestinal bleeding are discussed in detail. The modern pathogenetically substantiated methods of gastric mucosa protection based on the use of rebamipide, the GIT mucosal protector agent with proven efficacy, are proposed.